Improving Descriptive Text Reading Comprehension Using the SQ3R (Survey, Question, Read, Recite, Review) Method for Class VII-A Students at SMP Negeri 1 Lemola - Taluku, Meliaty Kristi; Sasabone, Carolina (Universitas Pattimura, 2024)
This study aims to improve the ability to read descriptive texts of students using the SQ3R method in the learning process. This research at SMP Negeri 1 Lemola. This study uses the classroom action research (CAR) method which focuses on how the SQ3R method improves students’ reading skills and uses data collection techniques namely observation, interviews, assignments and questionnaires. At the beginning of this study it was found that the students’ reading ability was lowdue to the ineffectiveness of the reading method used by the teacher. After using the SQ3R method, it shows that there is a change in students’ reading ability in each cycle. The test results used also show that more than 80% of students have achieved the achievement indicators. It is hoped that in the process of learning to read teachers can use more effective reading method to be able to improve students’ reading skills.